Work Life Balance of Women Faculty Working In HEIs with Special Reference to Bangalore City - M., Dr. Mathiyarasan; J., Dr. Chandrakhanthan; C., Mr. Dhanapal (RA Journal of Applied Research, 2023)
Women are demonstrating greater passion and interest in the educational area as technology advances, and they are finding it increasingly difficult to balance their personal and professional lives. The importance of a faculty member in educational institutions’ productivity cannot be overstated. To provide a high-quality service, they must be mentally and physically fit. The role of a faculty is very significant for the productivity of educational institutions. The majority of academics are women. As a result, it’s crucial to observe how these women manage their job and personal lives. In this context, the paper analyses the work life balance challenges faced by women faculty working in HEIs and impact of work life balance on women faculties’ performance in HEIs by using primary data. Through a literature analysis, the study chose three important factors that were appropriate for the study scenario. Workload, social support, and childcare were chosen as independent variables, whereas work life balance was chosen as the dependent variable. The primary data was collected via a standardized questionnaire by the researchers. In this article, a survey of 35 Bangalore educational institutions is undertaken using a sample of 220 instructors to determine the true state of work-life balance. The study finds that the work-life balance situation for female faculty members is moderate, which can be improved by providing flexible working hours, transportation, residential facilities, child care centers, flexible work arrangements/job sharing, reduced working hours and workload, and child schooling. The result of the research will be helpful for the HEIs administrators, to identify the importance of work life balance of female faculty in order to improve the outcome of their institutions.